Study of prognostic importance of hs-CRP levels in acute stroke patients coming to Theerthanker Mahaveer Medical College, Moradabad, Uttar Pradesh, India - Banthia, Bajranglal; Shakir, Saad Mohammad (International Journal of Research in Medical Sciences, 2020)
Background: Stroke has been found to be the fourth most fatal cause of death around the globe. Decreased activity and physical work are the major causes of increased incidences of stoke worldwide. It has also been studied that elevated levels of high-sensitivity C-reactive protein (hs-CRP) have been related to vascular inflammation whereas CRP is an important biomarker of systemic inflammation. Aim of this study to measure serum high-sensitivity C-reactive protein (hs-CRP) levels in the patients presenting with stroke, and evaluating its correlation as a prognostic marker in stroke patients. Methods: It was an observational prospective hospital-based case study carried out at Teerthanker Mahaveer Medical College and Research Centre, a tertiary care hospital situated in Moradabad, India for 5 months period from 1st November 2018 to 31st March 2019. 100 patients of new-onset stroke were included in the study. Results: According to the Scandinavian score, the majority of the patients who had ischemic stroke depicted a score range from 2-8. On the other hand, the majority the patients with hemorrhagic score had a Scandinavian score >14. The mean hs-CRP, when observed between different ranges of the Scandinavian score, showed that in 2-8 range the mean hs-CRP was 31.49±15.00, the mean hs-CRP for 9-14 range was 7.99±6.32 and the mean hs-CRP for >14 range was 7.10±0.32. Conclusions: It can be identified that levels of hs-CRP can be used as a marker to predict the long term prognosis of patients with stroke. In addition to this, it can also be identified that patients with higher levels of hs-CRP have lower Scandinavian score and the patients with lower hs-CRP levels have a higher Scandinavian score. Also, the results show that patients with ischaemic stroke have higher hs-CRP levels as compared to hemorrhagic stroke.